Castor oil - A more suitable feedstock for enzymatic production of methyl esters - E., Maleki; K., Aroua M.; N., Sulaiman N.M. (Fuel Processing Technology, 2013)
The yield of solvent-free enzymatic methanolysis of castor oil which is soluble in methanol was compared with soybean and palm oils that are low soluble in methanol. The comparison was performed under different operating conditions namely, enzyme dosage, solvent, and acyl acceptor. All reactions were performed at 45 C and agitation rate of 200 rpm for 24 h using lipozyme TL IM as catalyst. The yield of methanolysis of castor oil was remarkably high compared with soybean and palm oils especially at lower dosages of enzyme. Castor oil was the most effective oil with highest methyl ester yield of 67.58 at 15 of enzyme dosage. High yield of methanolysis of castor oil has been thought to be due to its solubility in methanol. Increasing the amount of enzyme improved the yield of methanolysis reactions to a maximum value followed by slight decrease at higher loadings of enzyme. However, enzyme dosage had slight influence on the yield of biodiesel from castor oil. Unlike palm and soybean oils, methyl acetate and tert-butanol didn't improve the yield of enzymatic transesterification for castor oil. The special behavior of castor oil has been thought to be due to presence of hydroxyl group in its structure.